Cytochromes P450 and species differences in xenobiotic metabolism and activation of carcinogen. - Lewis, D F (1998)
The importance of cytochrome P450 isoforms to species differences in the metabolism of foreign compounds and activation of procarcinogens has been identified. The possible range of P450 isozymes in significant variations in toxicity exhibited by experimental rodent species may have a relevance to chemical risk assessment, especially as human P450s are likely to show changes in the way they metabolize xenobiotics. Consequently, in the safety evaluation of chemicals, we should be cautious in extrapolating results from experimental animal models to humans. This paper focuses on examples in which species differences in P450s lead to significant alterations in carcinogenic response, and includes a discussion of the current procedures for toxicity screening, with an emphasis on short-term tests.